The anti-obesity and health-promoting effects of tea and coffee - Sirotkin, Alexander V; Kolesárová, Adriana (Physiological research, 2021)
This paper reviews provenance, chemical composition and properties of tea (Camelia sinensis L.) and coffee (Coffee arabica, L. and Coffeacaniphora, L.), their general health effects, as well as the currently available knowledge concerning their action on fat storage, physiological mechanisms of their effects, as well as their safety and recommended dosage for treatment of obesity. Both tea and coffee possess the ability to promote health and to prevent, to mitigate and to treat numerous disorders. This ability can be partially due to presence of caffeine in both plants. Further physiological and medicinal effects could be explained by other molecules (theaflavins, catechins, their metabolites and polyphenols in tea and polyphenol chlorogenic acid in coffee). These plants and plant molecules can be efficient for prevention and treatment of numerous metabolic disorders including metabolic syndrome, cardiovascular diseases, type 2 diabetes and obesity. Both plants and their constituents can reduce fat storage through suppression of adipocyte functions, and support of gut microbiota. In addition, tea can prevent obesity via reduction of appetite, food consumption and food absorption in gastrointestinal system and through the changes in fat metabolism.
Keywords: obezita; metabolismus lipidů; zdravotní stav; Coffee; Humans; Lipid Metabolism; káva; Anti-Obesity Agents; lidé; zvířata; fytonutrienty; hmotnostní přírůstek; čaj; Adiposity; Tea; Health Status; regulace chuti k jídlu; Appetite Regulation; Weight Gain; Obesity; Animals; látky proti obezitě; adipozita; Phytochemicals